Design and synthesis of a 3D flexible film electrode based on a sodium carboxymethyl cellulose–polypyrrole@reduced graphene oxide composite for supercapacitors. (26th March 2021) - Xu, Hanping; Li, Yue; Jia, Mengying; Cui, Linlin; Chen, Cheng; Yang, Yupeng; Jin, Xiaojuan
Abstract : A novel, environmentally friendly and freestanding 3D flexible film electrode (CMC–PPy@RGO) was prepared by a simple vacuum filtration method. Abstract : A flexible film electrode composed of sodium carboxymethyl cellulose (CMC), polypyrrole (PPy) and reduced graphene oxide (RGO) was designed by in situ polymerization and vacuum filtration. The obtained film displayed CMC–PPy nanospheres wrapped in an RGO framework, resulting in a free-standing and highly flexible supercapacitor electrode. The incorporation of hydrophilic CMC into the film enhanced the diffusion paths of electrolyte ions and prevented the volume deformation of PPy during the long-term charging/discharging. Furthermore, PPy provided a large pseudocapacitance and RGO endowed the film electrode with prominent flexibility. The remarkable interaction between CMC, PPy and RGO achieved a synergistic effect on the structural stability and electrochemical performance of the film electrode. When the mass ratio of CMC–PPy to RGO was 1 : 1, the highest specific capacitance of the sodium carboxymethyl cellulose–polypyrrol@reduced graphene oxide (S-CPR1 : 1 ) was 489 mF cm −2 (191 F g −1 ) with a mass of 2.56 mg cm −2 at a current density of 0.5 mA cm −2 . And the area specific capacitance of the S-CPR1 : 1 electrode could remain as 101.6% of the original value after 1000 charge/discharge cycles, which was higher than the polypyrrol@reduced graphene oxide (S-PR) electrode (72.4%) prepared under the same conditions. Besides, the S-CPR1 : 1 electrode exhibited remarkable flexibility with 95.6% capacity retention after 500 fold cycles. These above results indicated that the S-CPR1 : 1 film electrode provided a simple way of developing free-standing and flexible electrode materials for next-generation electrochemical electrodes.